Lista de mamíferos de Costa Rica - Rodríguez F., Javier; Chinchilla, Federico A (Revista de Biología Tropical, 1996)
An update of the 1983 checklist of Costa Rican mammals ineludes 223 terrestrial species, twenty of them new to the country (mainly Chiroptera). A total of 122 new locality records are reported in seven different 10caUties. The new records were taken from literature (53%); the Collection of Mammals ofthe Museo de Zoología, Universidad de Costa Rica (33%) and personal communications (11 %) mainly; 46% of the new records are previous to 1983.